Impact of social media on political participation of Egyptian youth - Tayie, Sally Samy (AUC Knowledge Fountain, 2014)
This study aims at examining the role played by social media in empowering and encouraging the Egyptian youth for political participation. Previous studies found that traditional media have not been influential enough to drive youth's political participation. On the other hand, recent studies found that social media have a significant role in this respect. The current study investigates the possible roles of the social media in the transition to democracy in Egypt; questioning the ability of social media to act as a platform where citizens are represented and empowered enough to transform virtual online discussions to real life actions. The study was carried out on a purposive sample of 400 young Egyptians aged 18-30 based on the statistics of social media users in Egypt. A sample of opinion leaders and elites in the field was also studied. The research follows a triangulation by combining two research methodologies; survey as a quantitative method and in-depth interviews as a qualitative one. The theoretical framework is Uses and Gratifications Theory. According to the findings of the study, social media became most prominent among youth in Egypt after January 25th Revolution. The study also found that most Egyptian youth use social media on a daily basis. Egyptian youth consider social media as a platform through which they manage to share their common concerns and possibly turn it into collective real-life actions; which reflects their interest in becoming more politically involved.